Serogroup W135 Meningococcal Disease, The Gambia, 2012 - M. Jahangir Hossain; Anna Roca; Grant A. Mackenzie; Momodou Jasseh; Mohammad Ilias Hossain; Shah Muhammad; Manjang Ahmed; Osuorah Donatus Chidiebere; Ndiaye Malick; S.M. Bilquees; Usman N. Ikumapayi; Baba Jeng; et al. (Emerging Infectious Diseases, 2013)
In 2012, an outbreak of Neisseria meningitidis serogroup W135 occurred in The Gambia. The attack rate was highest among young children. The associated risk factors were male sex, contact with meningitis patients, and difficult breathing. Enhanced surveillance facilitates early epidemic detection, and multiserogroup conjugate vaccine could reduce meningococcal epidemics in The Gambia.